Application of the Right of Refusal and Legal Liability in Journalistic Cases - Lumbanbatu, Indri Rovelia; Esther, July (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the application of the right of refusal by journalists and the legal liability arising in journalistic practice in Indonesia. The right of refusal is the right of journalists to protect the identity of sources who provide confidential information. Although regulated in Law No. 40/1999 on the Press, implementing the right of refusal often faces challenges, especially in criminal and civil law. This research uses a normative juridical approach by analyzing laws and regulations, case studies, and relevant court decisions. The results show that law enforcement officials have not fully recognized and respected the right of refusal, and they often force journalists to reveal the identity of sources. In addition, journalists often face lawsuits for their journalistic work, even though they have met the standards of professionalism and the journalistic code of ethics. This study concludes that protecting the right to refuse and legal certainty for journalists needs to be strengthened through revision of regulations, increased legal awareness, and consistent enforcement of the code of ethics. Thus, press freedom can be guaranteed without overriding balanced legal responsibility.